Analisis Usability Sistem Informasi E-Kinerja Di Dinas Komunikasi Dan Informatika Provinsi Sumatera Selatan Menggunakan Metode System Usability Scale (SUS) - Thirta, Pramudya Dhanu; Supratman, Edi; Amalia, Rahayu; Ariandi, Muhamad (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Information and communication technology plays an important role in facilitating many parts of everyday life. In the current digital era, almost all daily activities are related to technology, which has the benefit of making daily activities and activities easier. The South Sumatra Province Communications and Informatics Service, which has the main responsibility for supervising and advancing the communications and informatics sector under its jurisdiction, is implementing a governance system that currently includes E-Kinerja as an expression of governance. ASN's daily performance, which is related to additional compensation for employees, is evaluated using the E-Kinerja program. It is very important to implement an E-Kinerja strategy because some workers do not do their jobs well or according to their respective workloads. As a result, the public service system becomes slow, complicated and does not work ideally due to a lack of effectiveness, efficiency, transparency and accountability in the work carried out by employees. This research aims to assess the current condition of E-Kinerja in the South Sumatra Province Communication and Information Service, as well as propose realistic and evidence-based changes that will increase efficiency and effectiveness in workplaces and government services. The method the author uses is the System Usability Scale (SUS). The expected benefits of this research are that E-performance developers can use this research to develop applications according to user needs and further research can use this research as a reference in the field of usability analysis using the System Usability Scale (SUS).